The Senator, The Merchant, Two Carpenters, and a Widow: A Survey of Canadian Landlords in 1871 - Burley, David (Urban History Review / Revue d'histoire urbaine, 1997)
Recent scholarship has improved our understanding of the increase in home ownership in Canada from the late nineteenth century, but less attention has been directed to the group that owners displaced, landlords. With data sampled from the 1871 manuscript census, this study compares landlords and housing tenure in twenty urban centres of various sizes to reveal variations in housing markets, in the concentration of the ownership of rental accommodation, and in the relative attraction of housing investments for different people.By 1871 housing markets had already responded to industrial development, and landlords in Canada's major centres provided much more residential accommodation than in smaller communities. They also were drawn from different social backgrounds and were more likely in Toronto and Montreal than elsewhere to be artisans and tradesmen, to be younger, and less likely to be engaged in commerce. The market sensitivity of petty landlords qualifies assumptions about the inability of such investors to expand the housing of industrial cities.But, their limited resources did mean that they were unlikely to increase their participation in the housing market further. Nor was there much incentive for the major landlords in large centres — retired businessmen, gentlemen, bourgeois, and widows — to invest more: having retired, further investment required them to constrain their level of consumption and perhaps reduce their standard of living.